Policies and interventions to reduce injuries due to traffic accidents: From evidence to practice - Carmona Clavijo, Gloria (2018)
This article presents interventions to prevent mortality and injuries from traffic accidents (TA), from the scientific evidence and perspective of the actors involved. For this purpose, a systematic search was carried out, a policy summary was organized with the participation of key actors to finally carry out a deliberative dialogue with technical representatives of the various institutions related to the approach of the proposed problem. Describe evidence-based interventions related to education, integral infrastructure, pre-hospital assistance, regulations and control that were deliberate and contextualized to our local environment. The multi-sector technical representatives contributed considerations for its implementation, the potential benefits or damages, the use of resources, necessary adaptations, possible barriers and facilitators for its approach. It presents the channeling role that National Institute of Health developed to collaborate in the transfer of evidence to practice. It also raises research needs, which need to be addressed in comprehensive road safety interventions